Recombinant SARS-CoV-2 spike S1-Fc fusion protein induced high levels of neutralizing responses in nonhuman primates. Issue 35 (31st July 2020) - Ren, Wenlin; Sun, Hunter; Gao, George F.; Chen, Jianxin; Sun, Sean; Zhao, Rongqing; Gao, Guang; Hu, Yalin; Zhao, Gan; Chen, Yuxin; Jin, Xia; Fang, Feng; et al.
Highlights: CHO-expressed S1-Fc protein is very immunogenic in various animals and can rapidly induce strong antibody production. S1-Fc protein solicits strong neutralizing activities against live virus. Stable CHO cell line expressing 50 mg/L of S1-Fc, making it an accessible and affordable option for worldwide vaccination. Abstract: The COVID-19 outbreak has become a global pandemic responsible for over 2, 000, 000 confirmed cases and over 126, 000 deaths worldwide. In this study, we examined the immunogenicity of CHO-expressed recombinant SARS-CoV-2 S1-Fc fusion protein in mice, rabbits, and monkeys as a potential candidate for a COVID-19 vaccine. We demonstrate that the S1-Fc fusion protein is extremely immunogenic, as evidenced by strong antibody titers observed by day 7. Strong virus neutralizing activity was observed on day 14 in rabbits immunized with the S1-Fc fusion protein using a pseudovirus neutralization assay. Most importantly, in <20 days and three injections of the S1-Fc fusion protein, two monkeys developed higher virus neutralizing titers than a recovered COVID-19 patient in a live SARS-CoV-2 infection assay. Our data strongly suggests that the CHO-expressed SARS-CoV-2 S1-Fc recombinant protein could be a strong candidate for vaccine development against COVID-19.